Influence of Influencer Marketing on Brand Trust and Buying Decisions - Gunawan, Muhammd Fadhel; Dammar, Dwi Mawardi; Ifayanti, Ilmi; Nuryanti, Firisqi (Jurnal Economic Resource, 2025)
The rapid growth of social media has encouraged companies to adopt influencer marketing as a strategic tool to engage consumers and enhance brand performance. This study aims to examine the influence of influencer marketing on purchasing decisions, with brand trust acting as a mediating variable. A quantitative research approach was employed using a survey method, involving 150 respondents who actively use social media and have been exposed to influencer-endorsed products. The data were analyzed using Structural Equation Modeling (SEM) to test both direct and indirect relationships among variables. The results indicate that influencer marketing has a positive and significant effect on brand trust, suggesting that influencer credibility, authenticity, and expertise play a crucial role in building consumer trust toward endorsed brands. Furthermore, brand trust is found to have a significant positive effect on purchasing decisions, highlighting its importance in reducing perceived risk and increasing purchase confidence. Influencer marketing also directly influences purchasing decisions, demonstrating that emotional attachment and parasocial relationships with influencers can drive consumer purchasing behavior. The mediation analysis reveals that brand trust partially mediates the relationship between influencer marketing and purchasing decisions. These findings contribute to the influencer marketing literature by confirming the mediating role of brand trust and providing empirical evidence within the context of social media platforms. Practically, the results emphasize the importance of selecting credible and authentic influencers to strengthen brand trust and enhance consumer buying decisions